Inactivation of the Periaqueductal Gray Attenuates Antinociception Elicited by Stimulation of the Rat Medial Preoptic Area - Zhang, Yi-Hong (2007)
The medial preoptic area (MPOA) is a sexually dimorphic structure that plays key roles in gonado-steroidal regulation and thermoregulation. The MPOA may be involved in sex-based differences in nociceptive processing and steroid hormones effect on pain thresholds. Consistent with this, there is evidence that MPOA can produce antinociception or hyperalgesia. MPOA stimulation inhibits spinal cord or trigeminal neuronal responses to noxious stimuli or produces analgesia, yet most of these studies utilized electrical stimulation which antidromically activates periaqueductal gray (PAG) and rostroventromedial medulla (RVM) neurons involved in descending modulation of nociception. Effects of selective activation of MPOA neurons on behavioral indices of antinociception and the site-specificity of such responses are unknown. To address these questions, we examined the influence of MPOA microinjections of d, l homocysteate (DLH) on hindlimb and tail nocifensive reflexes in lightly anesthetized rats. DLH, but not saline, microinjections into several MPOA subregions markedly increased withdrawal response latencies to noxious thermal stimuli. Antinociceptive effects of MPOA activation were abolished by microinjection of lidocaine into PAG. These results suggest that activation of MPOA neurons produces antinociception that is at least partly mediated by projections to PAG.